Ruminant digestive systems closer look - Bishara, N.; Grant, Ron.; Creative Educational Video, Inc. (Lubbock, TX : CEV Multimedia, 2000)
Explains the basic anatomy and structures of ruminant digestive systems and the processes of digestion and absorption.
Fakulti Perubatan Veterinar
Title from disc surface.
Directed by Joseph N. Bishara.
Narrator, Ron Grant.
Keywords: Animal nutrition; Ruminants -- Digestive organs; Veterinary physiology